DEVELOPMENT OF CREATIVE ABILITIES OF STUDENTS AND ITS PROSPECTS - G‘aybullayeva Habiba Ismoilovna (Journal of new century innovations, 2022)
Annotation: in this article, an attempt was made to provide information on the topic of the development of creative abilities of students and its prospects.